(untitled) (Faridpur Medical College Journal, 2020)
Hypertrophic Cardiomyopathy (HCM) is the common monogenic form familial pathological cardiac hypertrophy. HCM is an important cause of sudden cardiac death in the young adult and a major cause of morbidity in the elderly. We discuss here the molecular genetics and recent advances in the molecular genetics of HCM. HCM became the first cardiac disease for which a molecular genetic mechanism was identified. More than 100 mutations in nine genes, that encoding sarcomeric proteins have been identified in patients with HCM, which had led to the belief that HCM is a disease of contractile sarcomeric proteins of the cardiac muscle. Approximately two-thirds of all HCM cases are caused by the mutation of the myosin heavy chain (MyHC), cardiac troponin T (cTnT) and myosin binding protein-C (MyBP-C). Genotype-phenotype correlation studies suggest that mutations in the MyHC gene are associated with more extensive hypertrophy and a higher risk of SCD as compared to mutations in genes coding for other sarcomeric proteins, such as MyBP-C and cTnT. However, there is a noteworthy variability and factors, such as modifier genes and probably the environmental factors affect the phenotypic expression of HCM. The results of different functional studies suggest that in spite of the variety of the mutations, the initial defects in HCM is abnormal cardiac myocyte function. In this era of genetics and upcoming future of precision medicine, good knowledge of its molecular basis of any disease is crucial for patient management, and HCM is not different. Faridpur Med. Coll. J. Jan 2019;14(1): 44-49